IDENTIFIKASI JENIS KAYU PADA RUMAH ADAT BATAK TOBA BERDASARKAN PERSEPSI MASYARAKAT DI DESA SIMANINDO KECAMATAN SIMANINDO KABUPATEN SAMOSIR - Simanjuntak, Chindy A.S; Sulaeman, Rudianda; Oktorini, Yossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
One of Batak Toba’s culture defensibility system is Museum of Batak Toba culture in Simanindo village, Simanindo Subdistrict, Samosir District which famous with Huta Bolon Museum. Batak Toba traditional housedominated by wooden materials. The ability of a specific wood type that is the main element in traditional house building is hard to be obtained that obstruct the construction and might threaten the existence and sustainability of the traditional house. The wood type used on Batak Toba traditional house building or wood type suitable to substitute the wood must be known, so that it could be preserved. The purpose of this research is to know the wood type used as the materials of Batak Toba traditional house on Huta Bolon Museum based on public perception. This research used snowball sampling method while the data collectedthrough observation and deep interview towards the informan. The data reduced become a summary which presented on brief description and descriptive qualitative approach for data analysis. Wood type used as the materials on Batak Toba traditional house construction in Simanindo villageused jior wood as the building foundation, attuang wood as the long wall (tustus ganjang), Pinus merkusii wood as the wall (balok ransang), ingul wood as the frame of the floor and as windows/doors, and rappa wood as the roof frame. Key Words:Batak Toba traditional house, snowball sampling, Identification.